Papal overlordship and European princes, 1000-1270 - Wiedemann, Benedict ca. 20./21. Jh. (Oxford Oxford University Press USA - OSO, 2022)
This study reinterprets the relationship between the medieval papacy and independent states, suggesting that kings and governments were able to increase their effective power through close relationships with the international papacy, making the papacy integral to the creation of centralized national states and kingdoms in Europe.
Description based on publisher supplied metadata and other sources
Keywords: Popes -- Temporal power -- History -- To 1500; Church and state -- Catholic Church -- History -- To 1500; Papacy -- History -- To 1309; Kings and rulers, Medieval; Church and state-Catholic Church-History-To 1500; Papacy-History-To 1309; Popes-Temporal power-History-To 1500; Electronic books